The Fama-French Three Factor Model and the Capital Asset Pricing Model : Evidence from the Indian Stock Market - Aggarwal, Ritika (Indian Journal of Research in Capital Markets, 2017)
The study aimed to provide empirical evidence on the validity of various asset pricing models for India. Specifically, it examined the behaviour of stock returns in relation to market beta, firm size (market equity), and book-to-market equity factors. I tested for the capital asset pricing model (CAPM), introduced by Sharpe (1964), Lintner (1965), Mossin (1966), and Black (1972) and then for a well-known extension to CAPM provided by Fama and French (1992), that is, the three factor model which moves away from the oversimplified relation between excess portfolio returns and excess market returns as prophesized by CAPM. I differed from the previous studies on this topic, in theÂ Indian market, in three significant ways. First, I constructed a higher number of portfolios to minimize variability within a portfolio. Second, I considered post-2008 stock market data, so as to exclude any impact of the economic crisis. Third, I also carried out a joint test on the constant term in the portfolio regressions using the GRS test statistic. Given the time period in consideration, the empirical tests conducted support the Fama-French three-factor model in explaining the variation of stock returns better than the single factor CAPM for the Indian stock market.